Regional disparities in the EU. Are they robust to the use of different measures and indicators? - Villaverde, José; Maza, Adolfo (Stockholm, 2011)
"The aim of reducing regional disparities in the European Union is enshrined in the EU Treaty. An important aspect that takes centre stage in discussions on the EU’s so-called cohesion policy is the ranking of the Union’s many regions in terms of their levels of prosperity. This ranking largely determines whether and by how much a region will be supported from the general budget. Crucially, regional prosperity and the ranking as such depend largely on how we measure disparities and development. This report discusses how regional disparities should be measured and what the EU ought to do in order to reduce these disparities."